Effects of Different Feeding Regimes on Survival and Growth of Medusa Shrimp Larvae (Latreutes anoplonyx) - Fakrajang, Siraprapa; Muthuwan, Vorathep; Kuandee, Prattana; Oungern, Doungtip; Taskkong, Chana (Burapha Science Journal, 2026)
The objectives of this study were to compare effects of different feeding regimes on survival and growth of medusa shrimp larvae (Latreutes anoplonyx). This experiment was divided into three different feeding regimes (CRD): rearing with Chaetoceros sp. 1.5x105 cells/mL and Brachionus sp. 5 individuals/mL (T1), Chaetoceros sp. 1.5x105 cells/mL and Brachionus sp. 3 individuals/mL combined with Artemia sp.1 nauplii/mL (T2), and Chaetoceros sp. 1.5x105 cells/mL, Brachionus sp. 3 individuals/mL and Artemia sp.1 nauplii/mL (T3). The results showed that mean survival rates were (+SE) 59.9+4.0, 66.7+3.9, and 66.7+6.7%, respectively (P>0.05). In addition, the highest mean total length was (+SE) 6.20+0.00 mm for rearing with T3 (P<0.05). The development from the first zoeal stage to post-larval stage was approximately 17, 15 and 15 days, respectively (P>0.05).